Sifat Efektuasi dalam Penerapan Great Leader Organization pada Rumah Makan Ma Ecot - Rega Ramadhan (Universitas Pendidikan Indonesia, 2022)
A great leader must be able to understand or be able to observe the behavior of his employees in an effort to encourage the performance and productivity of the employee even to make the employee a reliable person and become a leader. This study aims to identify how to recognize great leaders in a company or organization and how leaders deal with uncertain situations in the future. This research data collection technique is mainly for primary data, namely using the interview method. The object of research is the manager of Ma Ecot Restaurant, Mr. Asep Fahmi. The manager of the Ma Ecot Restaurant has proven that the value of effectuation in his leadership is in this Asep Fahmi man. Mr. Asep Fahmi as the manager of Ma Ecot Restaurant currently has five elements of value in effectuation. Keywords: great leader; effectuation; ma ecot restaurant; organization.